Three new species of Botanophila Lioy (Diptera: Anthomyiidae) from the Mexican Transition Zone - Gomes, Lucas R. P.; de Carvalho, Claudio J. B. (Zootaxa, 2021)
The genus Botanophila Lioy has several species distributed in North America, but none had been recorded from Mexico. Here we describe three new species of Botanophila from the highlands of the Mexican Transition Zone. We include images of habitus, drawings of the terminalia and a key to facilitate the identification of species. Remarkably, the male of the new species has dichoptic eyes, an unusual characteristic in Anthomyiidae.